Disulfiram inhibition of cyanide formation after acetonitrile poisoning. (2nd January 2016) - De Paepe, Peter; Colin, Pieter; Depuydt, Pieter; Decavele, An-Sofie; De Smet, Julie; Boussery, Koen; Stove, Christophe; Benoit, Dominique; Verstraete, Alain; Van Bocxlaer, Jan; Buylaert, Walter
Abstract: Context Cyanide poisoning may be caused by acetonitrile, a common industrial organic solvent and laboratory agent.Objective To describe the potential use of disulfiram in treating acetonitrile poisoning in a human clinical case and to further study its effect in human liver microsomes in vitro .Case details A 30-year-old man initially presented with a cholinergic toxic syndrome following ingestion of aldicarb. Toxicological analysis revealed coingestion of ethanol. He subsequently developed severe metabolic acidosis caused by the cyanogenic compound acetonitrile which was erroneously interpreted as acetone in the chromatogram. After three treatments with hydroxocobalamin (5 g i.v.) and sodium thiosulfate (12.5 g i.v.) on days 2, 3, and 5, he had transient improvement but recurrent lactic acidosis. Treatment with disulfiram was associated on day 7 with resolution of metabolic acidosis and slowing of the decrease in acetonitrile concentration. He recovered from acetonitrile toxicity completely. The time course of acetonitrile, thiocyanate, and cyanide concentrations suggested that disulfiram inhibited cyanide formation.Results In vitro experiments with human liver microsomes showed the cyanide concentration was significantly lower after incubation with acetonitrile and disulfiram than acetonitrile alone (a mean 60% reduction in cyanide level).Discussion Although disulfiram was given late in the course of the poisoning it is possible that it contributed to the recovery.